2019
DOI: 10.3390/ijerph16071193
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Race, Poverty, and Place in Disparities in Physical Activity

Abstract: Significant racial disparities in physical activity—a key protective health factor against obesity and cardiovascular disease—exist in the United States. Using data from the 1999–2004 National Health and Nutrition Examination Survey and the 2000 United States (US) Census, we estimated the impact of race, individual-level poverty, neighborhood-level poverty, and neighborhood racial composition on the odds of being physically active for 19,678 adults. Compared to whites, blacks had lower odds of being physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“… 3 , 4 Physical activity can prevent cardiometabolic disorders and improve immune function, mental health, and cognition. 5 , 6 Systematic reviews on the effects of physical activity interventions on the health of adults living with HIV have yielded promising results 7 , 8 ; thus, physical activity interventions that are tailored to the personal circumstances and preferences of AfAm YLWH are warranted. Although there are validated interventions that target improvements in HIV continuum of care outcomes, few of these interventions that are tailored specifically for AfAm YLWH, and to our knowledge, there are no such interventions that successfully target both HIV-related outcomes, such as antiretroviral adherence and viral suppression, in conjunction with physical activity goals among AfAm YLWH.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Physical activity can prevent cardiometabolic disorders and improve immune function, mental health, and cognition. 5 , 6 Systematic reviews on the effects of physical activity interventions on the health of adults living with HIV have yielded promising results 7 , 8 ; thus, physical activity interventions that are tailored to the personal circumstances and preferences of AfAm YLWH are warranted. Although there are validated interventions that target improvements in HIV continuum of care outcomes, few of these interventions that are tailored specifically for AfAm YLWH, and to our knowledge, there are no such interventions that successfully target both HIV-related outcomes, such as antiretroviral adherence and viral suppression, in conjunction with physical activity goals among AfAm YLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity is an established modifiable risk factor for the prevention and control of chronic diseases [ 16–20 ] and has been widely recommended as a strategy to enhance immunity [ 21 ] and reduce hospitalization and mortality related to COVID-19 [ 22 ]. POC are at highest risk for COVID-19 yet exhibit consistently lower physical activity compared to their White counterparts [ 23 , 24 ]. For example, a greater proportion of Black and Latino men (47% and 48%) and women (60% and 56%) are classified as insufficiently active, engaging in less physical activity than recommended, compared to non-Hispanic White men (39%) and women (45%) [ 25 ].…”
Section: Disparities In Covid-19 Physical Activity and Other Chronic Health Conditionsmentioning
confidence: 99%
“…The centuries of disadvantage and displacement of POC by Americans who are White have led to a population-wide differential advantage in terms of educational attainment, income, and accumulated wealth [ 28 ]. Although poverty is an enduring correlate of low physical activity levels [ 24 ], this relationship may be exacerbated for POC. Compared to POC, White people on average have higher educational attainment, earn more at the same level of educational attainment, and accumulate greater wealth, often enjoying wealth passed from previous generations, all of which are associated with more opportunities to be physical active [ 1 , 29 ].…”
Section: Societal and Systematic Roots Of Physical Activity And Chronic Disease Health Disparities Among Pocmentioning
confidence: 99%
“…Considering influences at the community and societal level, Smith et al [21] note that implementing community-based participatory research strategies, where community trust agents are engaged and community education on disease states is utilized, provide an opportunity to reach underserved populations and enhance their health outcomes. Social context is important in understanding racial disparities in physical activity [22]. The authors report that individual poverty and neighborhood poverty are associated with decreased odds of being physically active among both whites and blacks.…”
Section: Special Issue Emphasismentioning
confidence: 99%
“…However, inappropriate social and cultural behaviors toward racial and ethnical minorities in the US could lower the use of health promoting activities, and as a result, poor health outcomes such as obesity and diabetes could emerge. Hawes, Smith, McGinty, Bell, Bower, LaVeist, Gaskin and Thorpe [22] studied the role of race and ethnicity in performing physical activities. They found that black Americans are less likely to use physical health facilities when compared to white Americans.…”
Section: Reducing Racial Inequities In Health: Using What We Already mentioning
confidence: 99%